A note on efficient simulation of multidimensional spatial autoregressive processes. Issue 6 (3rd July 2017) - Otto, Philipp
ABSTRACT: In applications of spatial statistics, it is necessary to compute the product of some matrixW of spatial weights and a vector y of observations. The weighting matrix often needs to be adapted to the specific problems, such that the computation ofW y cannot necessarily be done with availableR -packages. Hence, this article suggests one possibility treating such issues. The proposed technique avoids the computation of the matrix product by calculating each entry ofW y separately. Initially, a specific spatial autoregressive process is introduced. The performance of the proposed program is briefly compared to a basic program using the matrix multiplication.